The Effectiveness of Eye Movement Desensitization and Reprocessing Toward Adults With Major Depressive Disorder: A Meta-Analysis of Randomized Controlled Trials - Yan, Shuya; Shan, Yanyan; Zhong, Shuming; Miao, Haofei; Luo, Yange; Ran, Hanglin; Jia, Yanbin (Frontiers in Psychiatry, 2021)
The practice-based evidence suggests that it is possible to use Eye movement desensitization and reprocessing (EMDR) to treat major depressive disorder (MDD), but its specific efficacy is unknown. A systematic search was carried out for randomized controlled trials comparing EMDR with a control condition group in MDD patients. Two meta-analyses were conducted, with symptom reduction as primary outcome and remission as exploratory outcome. Eight studies with 320 participants were included in this meta-analysis. The first meta-analysis showed that EMDR outperformed ‘No Intervention’ in decreasing depressive symptoms (standardized mean difference [SMD] =  0.81, 95% CI =  1.22 to  0.39, p = .0001, low certainty), but statistically significant differences were not observed in improving remission (risk ratio =1.20, 95% CI = 0.87 to 1.66, p=.25, very low certainty). The second showed the superiority of EMDR over CBT in reducing depressive symptoms (mean difference [MD] =  7.33, 95% CI =  8.26 to  6.39, p < .00001, low certainty), and improving remission (risk ratio = 1.95, 95% CI = 1.24 to 3.06, p = .004, very low certainty). Besides, anxiety symptoms and level of functioning couldn’t be included as secondary outcome due to the lack of data. The present meta-analysis suggests that EMDR is more effective in treating MDD than ‘No Intervention’ and CBT, particularly in individuals who have traumatic experience. However, this result should be considered with caution due to small sample size and low quality of trails.